The Threats of Heterogeneous and Fuzzy Variables Measurement in Research in Education - Pasikowski, Sławomir (Przegląd Badań Edukacyjnych (Educational Studies Review), 2017)
The aim of the article is to present the main threats to the validity of measuring the fuzzy variables and the variables characterized by a dynamic structure of the opposition. These threats are mainly due to inadequate modeling of this type of variables, routine choice of rating scales in the process of measurement design and the use of numerical methods unsuited to a verbal format of data in which these variables could be expressed. In the article the schemes of heterogeneous and fuzzy variables modeling were presented. These schemes are based on models developed in the theory of attitudes and on the system of fuzzy logic.